Analisis Praktik Giveaway dalam Jual Beli Online pada Perspektif Ekonomi Syariah - Utami, Rizky Ananda; Sugianto, Sugianto (Universitas Batanghari Jambi, 2024)
The purpose of this research is to determine the sharia economic perspective, disclosures made by 12Passtuff (Korean Outfit Medan Binjai) through online sales and purchases. Nowadays, online sellers implement various marketing strategies to attract customers and increase public awareness of their goods. This research uses a qualitative descriptive methodology. Data collection methods include document review, interviews, and/or observation. The search engine is 12Passstuff which uses the gift giving method in sales promotions by utilizing internet media for sales. The findings of this research reveal that there are no religious haram requirements in the competition held by 12Passtuff.